ELL targets c-Myc for proteasomal degradation and suppresses tumour growth - Yu Chen (Nature Portfolio, 2016)
The expression of the oncogene Myc is carefully controlled and dysregulation often leads to cancer. Here, the authors describe an E3 ligase for Myc—ELL—and show that it likely controls the ubiquitination and degradation of Myc.